MARRIAGE DISSOLUTION BASED ON ISLAMIC LAW OF EVIDENCE IN TERENGGANU STATE: ANALYSIS OF BLACK MAGIC CASES (International Seminar on Syariah and Law (INSLA), 2023)
This article examines the procedural adjudication of divorce cases involving allegations of black magic (sihr) through the framework of Islamic evidentiary laws. Specifically, it focuses on how the Terengganu Syariah Court Evidence Enactment 2001 can serve as a legal mechanism to prove the existence of supernatural elements in matrimonial disputes. The study outlines four primary objectives: first, to elucidate classical and contemporary scholarly opinions regarding the validity of divorce under the influence of black magic; second, to identify the specific typologies of magic that frequently precipitate marital breakdown; third, to evaluate the evidentiary methods and procedures utilized to confirm such divorces based on the Enactment; and fourth, to analyze practical case applications within the Terengganu Syariah Court. Employing a qualitative methodology, data for this study was gathered through a comprehensive literature review of legal statutes, religious texts, scholarly jurisprudence, and relevant case laws. The findings demonstrate that under the Terengganu Syariah Court Evidence Enactment 2001, methods such as confession (iqrar), testamentary evidence (shahadah or bayyinah), expert opinions (ra'y al-khabir), and decisive oaths (yamin) can be systematically applied to substantiate claims of black magic. By analyzing landmark cases such as Nurhisam bin Johari v. Shamliza binti Shafie, this paper illustrates how these evidentiary principles are deployed in judicial practice to ensure fairness, clarity, and reliability in complex supernatural disputes. Ultimately, this research provides the Syariah judiciary with critical insights into optimizing Islamic evidence acts when handling matrimonial cases intertwined with magical elements.